Penggunaan Perjanjian Tidak Tertulis Dalam Hubungan Kegiatan Bisnis - La Madi, Yuliana; Kuahaty, Sarah Selfina; Pariela, Marselo Valentino Geovani (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Article 1320 of the Civil Code, there is no provision requiring a written agreement as a condition for the validity of the agreement, in other words, oral agreements still have legal validity. Based on the concept of pacta sunt servanda which mandates that agreements must be obeyed. It can be seen in the case of compensation for fees for the ADB IPA procurement project between H. Mubin Raja Dewa as the plaintiff and Karlan A. Manessa in Palu City, various methods were used by the plaintiff to resolve the problem but the defendant did not show good faith.Purposes of the Research: As a result, the plaintiff filed a lawsuit demanding an unconditional refund. To find out and explain the legal consequences of using unwritten agreements in business relationships and to find out the form of responsibility of the parties for losses incurred as a result of the use of unwritten agreements in business relationships.Methods of the Research: The legal research method used for this research is based on primary, secondary and tertiary legal materials, and uses a statutory approach, a conceptual approach and a case approach.Results of the Research: The research results in this case, there are three forms of legal consequences, namely the emergence of a legal situation through an event which is alleged to be a legal act, the emergence of a legal relationship between two or more people and a legal entity, thirdly the emergence of sanctions if there is an action that is contrary to the law and based on the action. what has been done by Karlan A. Manessa must take individual responsibility for the violations he himself committed by paying compensation for the plaintiff's losses